2012
DOI: 10.1021/bi2016519
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electrostatic Interactions in Binding of Thrombin to the Fibrinogen γ′ Chain

Abstract: Thrombin binds to the highly anionic fibrinogen γ′ chain through anion-binding exosite II. This binding profoundly alters thrombin’s ability to cleave substrates, including fibrinogen, factor VIII, and PAR1. However, it is unknown whether this interaction is due mainly to general electrostatic complementarity between the γ′ chain and exosite II or if there are critical charged γ′ chain residues involved. We therefore systematically determined the contribution of negatively charged amino acids in the γ′ chain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(80 reference statements)
2
8
1
Order By: Relevance
“…With the exception of WT‐S2, all peptides prolonged the lag time and decreased the peak height of thrombin generation, confirming the overall anticoagulant effect of the fibrinogen γ′ chain. Notably, tyrosine sulfation considerably increased the potency of the peptide, in line with the notion that the two tyrosine residues of the γ′ chain are sulfated in vivo and play a critical role in the interaction with thrombin exosite II . Interestingly, in our assay the doubly sulfated peptide was a more potent anticoagulant than the doubly phosphorylated peptide, which has been used in previous studies .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With the exception of WT‐S2, all peptides prolonged the lag time and decreased the peak height of thrombin generation, confirming the overall anticoagulant effect of the fibrinogen γ′ chain. Notably, tyrosine sulfation considerably increased the potency of the peptide, in line with the notion that the two tyrosine residues of the γ′ chain are sulfated in vivo and play a critical role in the interaction with thrombin exosite II . Interestingly, in our assay the doubly sulfated peptide was a more potent anticoagulant than the doubly phosphorylated peptide, which has been used in previous studies .…”
Section: Discussionsupporting
confidence: 87%
“…Although the K d for the interaction of the (doubly phosphorylated) fibrinogen c′ peptide with thrombin exosite II has been estimated to be < 1 lmol L -1 [8,30], in our and other studies [11,32] much higher peptide concentrations were needed to show appreciable effects of the peptide on coagulation in plasma. Presently, we have no explanation for this discrepancy.…”
Section: No Peptidecontrasting
confidence: 60%
See 1 more Smart Citation
“…8 The more abundant gA isoform has a short C-terminal tail of 4 amino acids (gA408-411, AGDV) containing a platelet-binding site, whereas the less abundant g9 isoform has an extended C-terminal tail of 20 amino acids (g9408-427, VPREHPAETEYDSLYPEDDL) containing a highaffinity binding site for thrombin exosite II. [9][10][11] Random pairing of the g chain isoforms generates 3 types of fibrinogen molecules: gA/gA (85%-92%), gA/g9 (8%-15%) and g9/g9 (,0.5%).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of surface and active center charges of acetylcholinesterase in the electrostatic attraction of its ligands, and the influence of charge on the reactive orientation of the ligand has previously been demonstrated [6]. It was shown that electrostatics plays profound role in the thrombin-γ′ chain interactions [7]. The role of electrostatics on protein binding energy and its salt dependence was outlined in a series of other works [810].…”
Section: Introductionmentioning
confidence: 99%